Diplomatic Rhetoric Shaping Adaptation Funding-related Issues at the UNFCCC Negotiations (Bangladesh Journal of Public Administration, 2020)
In the contemporary world, the institutions that entangle states in certain obligations are crafted through multilateral negotiation processes. The Paris Climate Agreement provides one such glaring example. One of the vital issues of the Agreement, 'funding for adaptation’, which is crucial for the most affected countries like Bangladesh, received limited attention during the initial phases of the negotiations but emerged as a vital issue after a short time and quickly became a prominent issue. It finally ended up with a moderate profile in the Paris Agreement. How did the issues related to the Adaptation Fund emerge, and how were they framed-up, what was the mechanism of their evolution, and why did only some crucially-contested issues find traction? In this quest, this work extrapolates the framing theory from the media and communication domain and, through applying the approach, develops a simultaneous content and frame analysis, which leads to a historical mapping and tracing of the process of the evolution of the issues. It identifies a phenomenon of frame generation through the contested rhetoric framing of the actors in line with their primary logics, which were shaped by their original mental schemata and permeated throughout the negotiations. The work also identifies that the powerful actors determine the fates of the crucially-contested frames as well as their future implications. Keywords: Framing, climate negotiations, funding adaptation, power